Assaying Il Saggiatore, with a delicate and precise bibliographical balance - Nick Wilding; Jason W. Dean (Galilæana)
Il Saggiatore is bibliographically more complex than it might seem at first sight: copies can vary wildly in their parts and materials. The first edition has been repeatedly misdescribed in the book trade, with a fictitious “first issue” claiming chronological and monetary priority. The authors examine both a wide sample of copies and all the available supplementary documentation to establish the most useful way to describe and understand individual copies, and the entire edition, of this book.